Implementación de un portal web de lugares turísticos para la jefatura de turismo del cantón Latacunga utilizando herramientas open source y aplicando la metodología rad - Chicaiza Toaquiza, Erika Lorena (2013)
This research establishes a methodology to carry out the implementation of a Web portal of sights for the Tourism’s Head of the Latacunga Canton using Open Source tools and applying the methodology Rad, which allows you to display the distinctive places the Canton. The application was designed using free software tools such as the Joomla Content Management system that was used to make the site and the RAD methodology which has served to the development of the project, the same that has four stages to fulfill as are: (a) Phase of planning, (b) Design Phase, c) construction phase and d) phase of implementation. The application is composed by: the home page where people can find information that consists the goals, mission and vision, about turism, page of tourist sites detailing each one of the most emblematic places of canton, gallery of images in the same that you can view photos on the tourist sites, video gallery in which you may find various videos that show the characteristics of the Latacunga canton, gastronomy, festivals, tourist establishments and map of the routes. The research provides a valuable contribution to the institution for which it was created, as well as, for example to publicize the tourist sites, the use of technology for the dissemination of culture, the same that potentiated the cantonal development. It is important to mention the importance of research in the field of culture already which is a crucial element within the institutional practices of the Technical University of Cotopaxi as is the linking of the university with the people.